Pengaruh Komitmen Kerja dan Iklim Kerja Terhadap Kinerja Guru di SMA Ekasakti Padang - Caterina Caterina; Yulia Citra (Dinasti Research, 2023)
The purpose of this study is to describe and analyze the effect of work commitment and work climate on teacher performance at Ekasakti Padang High School. The population that was also studied was 19 teachers of Ekasakti Padang High School. The variables studied were work commitment and work climate as free variables and teacher performance as bound variables, data obtained from questionnaires and analyzed using regression with the help of the SPSS program with a significance level of 0.05. This research survey research. Survey research is research conducted on large or small populations, but the data studied is data from samples taken from that population and uses a questionnaire as the main data collection tool. The research method used is a quantitative analysis appoarch. The results of this study show that work commitment has a positive and significant effect on the family of teachers at Ekasakti Padang High School, as evidenced by the results of the regression analysis with a calculation = 4.805 and p = 0.000 < 0.05. The work commitment created in the Ekasakti High School environment is in the enough category. The work climate has a positive and significant effect on teacher performance at Ekasakti Padang High School, as evidenced by the calculation = 6,908 and p = 0.000 < 0.05. Work commitment and work climate have a positive and significant effect on teacher performance at Ekasakti Padang High School, as evidenced by Fhitung = 23,924 and p value = 0.000.